Novel lipase gene from Bacillus sphaericus 205y - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Chin, John Hun (2009)
A biologically pure culture of Bacillus sphaericus strain 205Y capable of producing an organic solvent - tolerant lipase was isolated from soil samples via direct plating method using 1 (V/V) of either benzene, toluene, or mixture of benzene and toluene as their sole carbon source, ethyl benzene and P-xylene. The lipase gene was isolated via genomic library and sequenced. The production of lipase gene from Bacillus sphaericus strain 205Y is a novel gene. The lipase gene was cloned from Bacillus spaericus strain 205Y and the recombinant lipase was efficiently excreted into the culture medium using expression vectors bearing the lipase gene.